CODE SWITCHING OF THE INDONESIAN-ENGLISH FOUND IN SELECTED PROFESSIONS’ UTTERANCES IN TALK SHOWS - Dahlia D. Moelier; Elysa Grata Lebang (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
Switching languages from one language to a different one has using by those who understand two or more languages. It then becomes a trend either in bilingual or multilingual society specifically in Indonesia. The aim of this study are to discover and analyze the types of code switching used by the selected professions in talk shows and reasons of those selected professions using code switching in their utterances. The data sources used in this study are selected talk show videos on YouTube. The data were obtained by downloading, transcribing, highlighting the utterances, and underlying the English phrases, clauses, or words. The writer used qualitative descriptive method and used Charlotte Hoffmann’s theory in analyzing the data. The results of this study showed that there were 3 types of types of code switching used by the selected professions, they are intrasentential, intersentential, and emblematic switching. There were also 5 reasons found why those selected professions using code switching in their utterances. They were talking about particular topic, quoting somebody else’s statements, being emphatic about something, interjection, and repetition used for clarification. The reasons of express group identity and clarifying the speech content for the interlocutor are not found